Metabolome analysis of Eriocheir sinensis serum under air exposure at low temperature - Mengqi Ni; Shucheng Shao; Zhaoxia Cui (Aquaculture Reports)
Air exposure is a common stressor that disrupts the physiological activities of aquatic crustaceans. Low temperature can effectively alleviate the stress caused by air exposure. The study investigates the metabolic response of Eriocheir sinensis to air exposure at low temperature using serum metabolomics. Exposure to the stress induces increase in tricarboxylic acid (TCA) cycle intermediates and phospholipids. This metabolic shift is crucial for enhancing energy production and facilitating dynamic remodeling of the cell membrane. And the enrichment of the hypoxia-inducible factor-1 (HIF-1) signaling pathway and the ATP-binding cassette (ABC) transporter pathway suggests the activation of signal transduction processes. Moreover, the enhanced activities of autophagy, efferocytosis, and the Forkhead Box (FoxO) signaling pathway reflect the reinforcement of the immune defense mechanism. These results clearly indicate that E. sinensis can correspond to the stress through multi-dimensional regulation. This study can provide theoretical basis for in-depth understanding of the environmental adaptation strategies of E. sinensis and offer valuable references for the scientific management during its cultivation and transportation.